Hubungan Karakteristik Perawat dengan Tingkat Pengetahuan mengenai Ventilator Associated Pnemonia (VAP) di Ruang ICU dan ICCU RS Husada Jakarta - ojs, admin; Juliani, Enni; Rosliany, Nia; suharni, Suharni (Sekolah Tinggi Ilmu Kesehatan RS Husada, 2018)
Associated Ventilator Pneumonia (VAP) is defined as pneumonia that occurs 48 hours or more after a mechanical ventilator is administered. Associated Ventilator Pneumonia (VAP), is the most common form of nosocomial infection encountered in intensive care, especially in patients who use mechanical ventilators (Wiryana, 2007). The purpose of this study is to know the relationship of nurse characteristics to VAP knowledge level in ICU / ICCU Room of Husada Hospital, Central Jakarta. The results showed that there was a significant correlation between age, duration of work, education level with nurse knowledge level about VAP (p value <0,05). Nurses need to improve their ability to use mechanical ventilators to improve the quality of nursing care.